No myopic loss aversion in adolescents? An experimental note - Daniela Glätzle-Rützler; Matthias Sutter; Achim Zeileis (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2013)
Myopic loss aversion (MLA) has been found to play a persistent role for investment behavior under risk. We study whether MLA is already present during adolescence. Quite surprisingly, we find no evidence of MLA in a sample of 755 adolescents. This finding is at odds with previous findings, and it might be explained by self-selection effects. In other dimensions, however, we are able to replicate stylized findings in our pool of adolescents, such that teams invest higher amounts than individuals and that women invest less than men.
Keywords: C91; D03; 330; myopic loss aversion; experiment; adolescents; team-decision making